Tin Oxide Film Deposition and Characterization for a Chemoresistive Gas Sensor. Issue 4 (3rd July 2016) - Velmathi, G.; Mohan, S.; Henry, Rabinder
ABSTRACT: The proposed work studies the synthesis, structural, and sensitivity of tin oxide films deposited by sputtering for a gas sensor. This includes an analysis of a tin oxide film doped with noble metal palladium. Gas sensitivity of the deposited layer is analysed as per the deposition parameters such as the thickness of the film, substrate temperature, argon–oxygen ratio of the sputtering environment, and duration and doping metal weight percentage into the tin oxide films and the results obtained are explained.